EFFECT OF REARING SEASONS ON THE ECONOMIC PARAMETERS OF CROSSBREED SILKWORM BETWEEN SAMIA RICINI AND SAMIA CANNINGI - DULUR BRAHMA, (International Journal of Pharma and Bio Sciences, 2015)
Samia ricini and S. canningi are non-mulberry silk worms with multivoltine and bivoltine nature reared indoor and outdoor, respectively. Both the varieties are found in the North-eastern states of India. S. ricini is susceptible to unhygienic and poor environmental conditions. The present study was designed to produce a crossbreed between S. ricini and S. canningi and to study the effect of seasonal variation on the rearing performance between the F1 hybrid and the parents. Experimental results have shown that the rearing performance of crossbreed showed superior quality compared to parental species. Temperature fluctuation was found to be the major factor in the rearing performance. The present study, therefore, suggest that the S. ricini x S. canningi crossbreed may be a good variety for silkworm industry whose productivity can be increased by taking good care of temperature fluctuation. However, further study regarding the productivity and temperature needs to done to establish the correlation.